Fatores genéticos na psoríase glossite migratória benígna: Revisão da literatura sobre a associação com o complexe HLA - Gonzaga, H. F S [UNESP]; Torres, E. A.; Cardoso, A. L P; Ramalho, R. B.; Alohorne, M. M A; Gerbase-de-Lima, M. (My University, 1998)
The genetics of psoriasis and benign migratory glossitis has relationship with the major HLA. The authors reviewed the literature about the association between HLA with psoriasis and benign migratory glossitis. HLA-Cw6 presents a particularly strong association, irrespective of different racial or ethnic groups, suggesting that Cw6 itself, or a closely linked gene in strong linkage disequilibrium, is the major HLA-linked susceptibility gene for psoriasis. The white Brazilian population shows the established associations between psoriasis and the HLA antigens Cw6, B13 and B17 reported in several Caucasian populations, and shows association between benign migratory glossitis and HLA-Cw6.
Genetics factors of psoriasis and benign migratory glossitis: Review of literature about relationship with major HLA
Keywords: Benign migratory glossitis; Hla antigens; Psoriasis